Labor gymnastics proposal based on the Pilates Method: an integrative review (Research, Society and Development, 2022)
Introduction: The search for quality of life at work has been arousing the interest of researchers. The labor gymnastics has been widely used as a management strategy in the worker's health, both in private companies and in public institutions; in view of a growing trend on the use of the Pilates method in anti-stress activities at work motivated this study. Objective: In order to investigate in the literature if interventions with labor gymnastics based on the Pilates method can provide improvements in the levels of occupational pain and/or stress, enabling a reduction in the rates of absenteeism from work. Methods: To this end, a search was conducted in the BVS, Pubmed, and Scielo databases for original articles dated 2011-2020, relating the main results on quality of life, labor gymnastics, use of the Pilates method, and reduction of absenteeism rates at work, following the inclusion and exclusion criteria. Results: At the end of the study it was observed that the Pilates method has been used as a therapeutic resource associated with labor gymnastics to reduce chronic pain, occupational stress and reduce absenteeism at work.